Organic Farming’s Impact on the Environment: The Controversy - Mohan, Ishani; Paul, Rishav; Kumar, Nadam Akshay; Kaushal, Shilpa (International Journal of Economic Plants, 2022)
Organic farming is usually regarded to be more environmentally friendly than conventional farming. On this subject, we perform a global literature review. Organic farming employs integrated production practises that reduce the environmental impact of inorganic fertilisers, herbicides, and genetically modified organisms. In terms of environmental and climate change effects, organic farming is less polluting than conventional farming when measured per unit of land. Organic cuisine is gaining popularity around the world. The main driver of increased demand is consumer concern about the detrimental impacts of conventional agriculture on the environment and human health. All across the world, various organic agricultural practises are practised. They are united by common aims of economic, environmental, and social sustainability. Many countries currently have specific legislative underpinnings for organic farming, as well as production and processing certification programmes. The expansion of organic agriculture practises and markets demonstrates how this is a viable alternative to intensification. More political will and scientific money could help realise more of this potential. In addition to developing organic agriculture, this should inform and improve the sustainability of other forms of agriculture.